SUMATRA FAULT SLIP RATES ANALYSIS WITH DISLOCATION ELASTIC METHOD - ARINI - NIM: 25116301 , DWI
Sumatra is one of active seismogenic zone on the earth that produces seismotectonic and faulting systems along the Sumatra Fault System (SSS). Divided into several segments with a record of large earthquakes that occurred in segments around West Sumatra, namely in the Siulak segment 1909 (Ms = 7.6), 1995 (Mw = 7.0), Suliti 1943 (Ms = 7.4), Sumani 1926 (Ms ~ 7), 1943 (Ms = 7.6), Sianok 1822, 1926 (Ms ~ 7). From that earthquake hystories, it is necessary to measure the slip rates in West Sumatra to determine the level of fault activity. This research was carried out with the stages of coordinate calculation and time series to produce velocity vectors indicating plate movement patterns that occurred in Sumatra and modeled using the elastic dislocation method. As the result, velocity vector shows that the pattern of subduction movements is more dominant causing movement activities in the Mentawai area and West Sumatra. The velocity vector in the Mentawai area is larger with a value of 30.25 mm / year in the east-west direction and 25.97 mm / year in the north-south direction compared to the velocity vector that occurs around the Sumatra Island with a value of 27.4 mm / year directed east - west and 11.58 mm / year for north-south direction. The value of distribution slip area near subduction has a maximum value of 0.1 m, with an average is 0.03 m and has a 100% coupling (fully coupled) in the area around -2 ° N on the Mentawai island for areas with data usage only on the Mentawai Island. 100% coupling also occurs in the area of 0-3 ° N and around -4.2 °N for Mentawai Island and the area near the fault data. Direction of slip is in the same line of subduction direction system. This fully coupled area is indicated in energy accumulation period that has potential for a further large earthquake.